'Gendering' the text through implicit citations of gendered discourses: the construction of gender and teacher talk around children's fiction. (10th May 2018) - Namatende-Sakwa, Lydia
Abstract : This study departs from the overriding focus on textbooks, which disregards how readers take them up. Informed by feminist post-structural theory, I analyse the construction of gender in children's fiction texts used in a New York City elementary school. First, I demonstrate that while the children's fiction texts were explicitly female dominated and/or progressive in their construction of gender, a feminist post-structural discourse reading illuminated that they in fact, implicitly cited discourses, which maintained gendered binary constructions and male dominance. Second, in going beyond the text, the study demonstrates that far from ignoring gender to focus on the 'official' curriculum as explicitly affirmed by the teachers, they had in fact implicitly and inadvertently cited, invoked and deployed discourses and discursive practices that inscribed gender differential and hierarchical relations in the use of the texts in the classroom. Third, I provide insights into teachers' lack of awareness regarding how gender is cited in their texts, and enacted in their teaching practices. I argue therefore that this 'talk around the text', which illuminated gendered discourses and practices, is, as well articulated by Jane Sunderland, 'an excellent epistemological site' for the deconstruction of traditionally gendered positions in the classroom.